Determination of immune reactive proteins in Hydatid Cyst that isolated from sheep in Kerbalaa province- Iraq - Obead, Jihad Talib; Alkafaji, Nada Abdulhussein; Khudair, Sajad adnan; Sulbi, Ihsan Mohammed (Technium BioChemMed, 2025)
Hydatidosis is among the most common parasitic zoonotic diseases, not just in Iraq but globally. Worldwide, in domestic animals and humans are at significant effect for unilocular hydatid disease, This is brought on by the parasite E. granulosus. The zoonotic parasitic disease known as cystic echinococcosis, brought on by the tapeworm E. granulosus. Through development of parasite, dogs and carnivores serve as the final hosts, whereas herbivores and omnivores, such as humans, serve as intermediated hosts, where the metacestode (larval stage) grows in the organs, primarily the lungs and liver. Although sheep have lately drawn increased attention as E. granulosus infection reservoirs among intermediate hosts, the understanding of the localized inflammatory responses associated with liver cystic echinococcosis is limited Echinococcus granulosus larvae, known as hydatid cysts, are frequently seen in Iraqi sheep and goats that have been killed. Our study's objective was to identify immune reactive proteins in hydatid cysts extracted from infected sheep's liver. In this investigation, samples of liver from sheep slaughtered at the Karbala Abattoir in Iraq were used to acquire fluid from Hydatid cysts (N = 25 samples). The SDS-PAGE technique (Sodium Dodecy Sulfate-Polyacrelamide Gel Electrophoresis) was used to analyze different proteins in the fluids extracted from cysts in order to identify reactive proteins. The fluid antigens' SDS PAGE results showed 85 kDa, 70 kDa, 46 kDa, 34 kDa, 23 kDa, 9 kDa, 4 kDa, and 2 kDa bands for hydatid cysts. Conclusion of current study, improve our understanding of immune responses to cystic Echinococcosis in intermediate hosts, identify disease progression markers, and offer initial insights for future research on hydatid cyst immune reactions